How health seeking behavior develops in patients with type 2 diabetes: a qualitative study based on health belief model in China - Du, Qiu-hui; Zhang, Zi-chen; Yang, You; Luo, Xiao-xi; Liu, Li; Jia, Hong-hong (Frontiers in Public Health, 2024)
Background: Type 2 diabetes(T2DM) is a global health problem which is accompanied with multi-systemic complications, and associated with long-term health burden and economic burden. Effective health seeking behavior (HSB) refers to reasonably utilize health resources, effectively prevent and treat diseases, and maintain health. Effective health seeking behavior (HSB) is vital to mitigate the risk of T2DM complications. However, health seeking behavior for T2DM patients remains sub-optimal worldwide. Objective: The study aimed to explore the internal logic of how health seeking behavior of T2DM patients develops and the influencing factors of health seeking behavior. With a view to provide a reference basis for improving the health seeking behavior situation of T2DM patients. Methods: This study was conducted at an integrated tertiary hospital in China. People who were diagnosed with T2DM, capable of expressing clearly and had no mental illness, were approached based on a purposive sampling. The experience of T2DM and health seeking behavior were collected via in-depth interviews. A theory-driven thematic analysis based on Health Belief Model (HBM) was applied for data analysis. Inductive reasoning was used to identify emerging themes which were not included in HBM. Results: 26 patients with T2DM were included in the current study. Seven themes were identified, including: 1) T2DM diagnosis and severity; 2) T2DM treatment and management; 3) Perceived susceptibility of diabetes progression; 4) Perceived severity of diabetes progression; 5) Perceived benefits of health seeking behavior; 6) Perceived barriers of health seeking behavior; 7) Perception of behavioral cues. Generally, patients with T2DM lacked reliable sources of information, considered T2DM to be slow-progressing and without posing an immediate threat to life. Consequently, they did not fully grasp the long-term risks associated with T2DM or the protective effects of health seeking behavior. Conclusion: This study highlighted the challenges in health seeking behavior for patients with T2DM. It suggested that future interventions and strategies should involve multi-faceted approaches, targeting healthcare providers (HCPs), patients with T2DM, and their support networks. This comprehensive strategy can help patients better understand their condition and the importance of effective health seeking behavior. Ultimately, enhancing their capacity for adopting appropriate health-seeking practices.